2007
DOI: 10.1007/s11595-006-4749-8
|View full text |Cite
|
Sign up to set email alerts
|

Activity and structure of calcined coal gangue

Abstract: Coal gangue was activated by means of calcination in seven temperature ranges. Systematic research was made about activation mechanism and structural evolution. Glycerin-ethanol method, SEM, MIP and XRD were used to determine the variation of structure and activation of coal gangue during the calcination. The experimental results show that because of heat treatment in the range of calcination temperature, mineral composition and microstructure of coal gangue are changed. In addition, its activity is improved e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Previous studies on coal mining waste have demonstrated the potential for its use in alkali-activated material since it is rich in silicon and aluminum (6)(7)(8). However, pre-treatment processes are required (6,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on coal mining waste have demonstrated the potential for its use in alkali-activated material since it is rich in silicon and aluminum (6)(7)(8). However, pre-treatment processes are required (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on coal mining waste have demonstrated the potential for its use in alkali-activated material since it is rich in silicon and aluminum (6)(7)(8). However, pre-treatment processes are required (6,9). The aim of this research was to evaluate the influence of three different wastes on the mechanical performance and microstructural development of AAM, since the chemical, physical and mineralogical characteristics play an important role in this regard (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resíduos de carvão são materiais heterógenos, suas características físicoquímicas e mineralógicas dependem do tipo de formação geológica presente na região de extração, mas geralmente apresentam minerais de quartzo, caulinita, ilita, pirita, são compostos quimicamente em maiores teores por SiO2 e Al2O3, apresentando teores menores de Fe, S, Ca e Mn (GONG et al, 2007;CAO et al, 2016;CRUTANEO, 2016), portanto os resíduos de mineração de carvão são aluminoso silicatos inseridos em fases minerais, com pouca ou nenhuma reatividade, necessitando de processos de prétratamento para prover maior teor de fases vítreas ou amorfas (GONG et al, 2007).…”
Section: Referencial Teóricounclassified
“…Despite the aforementioned possibilities of using coal shale, new and more rational methods and technologies of its management are continually being looked for [9,10]. Due to the poor pozzolanic activity of shale rock, it is necessary to subject it to the thermal processing of calcination [11,12,13,14,15]. During the calcination process of waste coal shale, dehydroxylation of clay minerals, such as kaolin, occurs.…”
Section: Introductionmentioning
confidence: 99%